2002
DOI: 10.1210/endo.143.2.8623
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Secondary β-Cell Failure in Type 2 Diabetes—A Convergence of Glucotoxicity and Lipotoxicity

Abstract: Chronic hyperglycemia and hyperlipidemia can exert deleterious effects on beta-cell function, respectively referred to as glucotoxicity and lipotoxicity. Over time, both contribute to the progressive deterioration of glucose homeostasis characteristic of type 2 diabetes. The mechanisms of glucotoxicity involve several transcription factors and are, at least in part, mediated by generation of chronic oxidative stress. Lipotoxicity is probably mediated by accumulation of a cytosolic signal derived from the fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
104
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(118 citation statements)
references
References 35 publications
3
104
0
4
Order By: Relevance
“…Palmitate is toxic to beta cells through multiple, incompletely understood mechanisms [3,4]. Intriguingly, palmitate decreased TXNIP production, rather than increasing it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmitate is toxic to beta cells through multiple, incompletely understood mechanisms [3,4]. Intriguingly, palmitate decreased TXNIP production, rather than increasing it.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the deleterious effects of glucose on beta cell function and survival are not entirely clear but are thought to involve oxidative stress induced by increased nutrient flux, leading to excessive generation of free radicals [3,4]. The balance between free radical generation and the capacity of antioxidants to scavenge them determines the degree of oxidative stress exerted on the beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that diabetes is characterised by insufficient beta cell adaptation to insulin resistance [15,21,22] followed by beta cell failure. While there is increasing evidence suggesting that glucose plays a critical role in beta cell failure [23,24,25,26,27], the role of glucose during the early phase of insufficient adaptation has been the subject of much debate. Some authors have proposed that glucose is the primary regulator of beta cell mass and function in vivo, whereas others have noted beta cell adaptation in the absence of hyperglycaemia [5,6,8,10,15,28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycaemia induces phenotypic alterations of rodent beta cells, including GSIS abnormalities, reduced expression of specific genes (loss of beta cell differentiation), hypertrophy, slight increase in apoptosis, and increased expression of genes normally repressed in fully differentiated beta cells [6,[8][9][10][11][12][13][14]. These phenotypic alterations may contribute to the progressive worsening of GSIS in type 2 diabetes [15,16].…”
Section: Introductionmentioning
confidence: 99%